Further investigations towards luminescence dating of diatoms. (August 2022) - Morthekai, P.; Tiwari, P.; Murari, M.K.; Singh, P.; Thakur, B.; Manoj, M.C.; Ali, S.N.; Singh, V.K.; Kumar, K.; Rai, J.; Dubey, N.; Srivastava, P.
Abstract: Following up on previous attempts to date diatom frustules, further investigations were made on 1) extracting diatom frustules devoid of inorganic luminescent grains, 2) developing an equivalent dose estimating protocol based on the diatomite luminescence characterization, and 3) testing the applicability of this protocol on two lacustrine profiles. Diatom frustules were extracted in such a way that they are almost devoid of non-biogenic polymineral grains, confirmed by field emission scanning electron microscope (FE-SEM) observation and energy dispersive X-ray (EDX) analysis. The presence of opal was confirmed by X-ray diffraction (XRD) spectrometric analysis. The optimized luminescence signal that could be used for equivalent dose estimation was blue stimulated UV emission with a preheat temperature of 200 °C. The thermoluminescence glow curve peaking at 245 °C might be the source of this signal. In this study the characteristic dose was found to be ∼1500 Gy. Two sediment profiles were explored for luminescence dating, fading rates and a-values were found different between profiles. This discrepancy can be resolved 1) by measuring luminescence characteristics across different regions, or/and 2) by using species-specific luminescence measurements. This attempt has yielded an encouraging set of luminescence ages, with diatom frustule ages comparable to fine grain polymineral ages. Highlights: Diatom frustules extracted from the samples and are free from non-biogenic dosimeters. Luminescence properties characterized and protocol refined for age estimation. Diatom frustules age comparable (43%) with that of fine-grain non-biogenic sediment.